Habitat requirements of nymphaeids in humic lakes of the Wielkopolska region (western Poland) - Gąbka, Maciej (Biodiversity: Research and Conservation, 2006)
The study analyses habitat requirements of the associations with Nuphar lutea (L.) Smith, Nymphaea alba L. s.s. and the cross-breed forms of Nymphaea xborealis Camus (N. alba x N. candida). The study comprised 15 highly coloured and rich in humus substances lakes of the Wielkopolska region. Altogether, 21 water and 16 substrate properties were analysed in the patches dominated by the studied nymphaeids. The former involved a wide spectrum of factors related to the hardness of water and nutrients concentration. Factors related to the hardness of substratum were decisive for the habitat differentiation of the associations of analysed species.